THE ROLE OF INFORMATION COMMUNICATIONS IN THE TRAINING OF CIVIL ENGINEERS - Akhmedov Islombek; B.Sharopov (Journal of new century innovations, 2023)
Abstract. New modern programs developed for modern construction directions play a huge role in improving the knowledge and skills of construction engineers.